Pendampingan Sekolah Online Siswa Sekolah Dasar Melalui Kegiatan SIPUNG (Sekolah Ing Kampung) Pada Masa Pandemi Covid 19 Sebagai Solusi Mengatasi Pendidikan Di Desa Nguling-Pasuruan - Nurin Nazlah; Wahyu Djoko Sulistyo (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Social problems are problems that are deeply rooted in every country, including Indonesia. This problem penetrates into all fields, one of which is education. Plus the COVID-19 pandemic situation has also brought up many new problems in the world of education. The learning that was applied during this pandemic made a new learning transformation from what was originally offline to online. 80% of all parents of SDN Nguling I, II and III state that their children have difficulty understanding the material when learning online. Online School Assistance through SIPUNG is a concrete solution to improve the quality and understanding of student learning during online learning. By using the service learning method, it is proven to be able to improve the quality and understanding of students, students understand the importance of learning and parents are increasingly aware of the importance of providing the best assistance in order to achieve the success of children's education.